1988
DOI: 10.1109/61.4304
|View full text |Cite
|
Sign up to set email alerts
|

Scaled low-voltage side surge current tests on a model distribution system

Abstract: A series of scaled low-voltage side surge current tests were conducted on a model distribution system. The tests revealed the most significant circuit parameters effecting the magnitude and distribution of currents that will flow in a customers wiring.The tests also showed that distribution transformers utilizing interlaced windings rated 240/120 volts are unlikely to significantly increase the magnitude of surges in comparison to noninterlaced windings of the same rating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…On the other hand, the voltage between 2 and 0 terminals . It is confirmed that the interlaced winding of the secondary side is effective for the reduction of the impulse voltage occurring at the secondary windings (4) . ( 2 ) Case 2 Figure 17 shows the voltage distribution of the secondary windings in Case 2.…”
Section: Influence Of Wavefront Time Of Injected Currentmentioning
confidence: 67%
“…On the other hand, the voltage between 2 and 0 terminals . It is confirmed that the interlaced winding of the secondary side is effective for the reduction of the impulse voltage occurring at the secondary windings (4) . ( 2 ) Case 2 Figure 17 shows the voltage distribution of the secondary windings in Case 2.…”
Section: Influence Of Wavefront Time Of Injected Currentmentioning
confidence: 67%
“…The core type of transformer construction with the interlaced winding is known t o eliminate such low-voltage side surge failures; however, this type of construction could cause higher overvoltages to appear in the c o~e c t e d customer's apparatus than in the non-interlaced windings case 1101. The insulation coordination of a distribution transformer not only should eliminate the failures due to low-voltage side surges but also minimize the overvoltages transferred on to the apparatus connected to the secondary windings of the transformers [9,10]. The surge voltages transferred into the secondary of the transformer have been studied very little [ll-131. In view of the problems associated with the overvoltages appearing in the secondary winding due to surge transfer phenomena or to a surge impinging directly on the secondary line terminals, it is essential t o evaluate the transient response of the secondary windings.…”
Section: S Jayaram and H S Chandrasekharaiahmentioning
confidence: 99%
“…Overvoltage studies can present a considerable variety of possibilities of modeling of low-voltage power installations (LVPI) in distribution systems, either in laboratory experimental setups or in digital simulations. In (Mcmillen et al 1988 ; Dugan and Smith 1988 ; Smith and Puri 1988 ; Goedde et al 1992 ; Hosfet et al 1992 ; Standler 1992 and Mirra et al 1997 ) the consumers are represented by lumped resistances or capacitances or simple association of them. In (Borghetti et al 2005 ) it was used the matching impedance of the low-voltage line for representing the consumers.…”
Section: Introductionmentioning
confidence: 99%